P076 A bioassay to measure tgfΒ activity reveals decreased tgfΒ activity in systemic sclerosis serum. (21st February 2018) - van Caam, A; Vitters, E; van den Hoogen, F; Vonk, M; van der Kraan, P
Abstract : Introduction: Systemic sclerosis (SSc) is a severe disease characterised by auto-immunity, vasculopathy and excessive fibrosis of connective tissues. The pathophysiology of SSc is still poorly understood, but its symptoms imply a role for dysregulated transforming growth factor β (TGFβ) signalling because this cytokine is known to regulate vascular and connective tissue biology. TGFβ circulates in blood in an inactive latent form bound to latency associated peptide and latent TGFβ binding proteins. This latent TGFβ has to be activated before it can become bioactive. With the use of a bioassay TGFβ's bioactivity can be measured in complex mixtures like serum. This is not possible with an ELISA because this technique does not take (cellular) activation processes into account. Objectives: To determine the bioactivity of TGFβ in SSc serum compared to that of healthy control serum. Methods: Serum was collected of 10 SSc patients and 10 age and sex matched healthy controls. Primary human fibroblasts of 3 donors were transduced with CAGA12 -luc which produces luciferase in response to TGFβ/Smad3 or BRE-luc which produces luciferase in response to BMP/Smad1/5. These cells were treated with 10% serum for 16 hour and luciferase activity was measured. To activate all TGFβ, sera were treated with 4M HCl for 1 hour at RT, after which pH was normalised with 4M NaOH. Controls were treated with HCl and NaOH simultaneously. To verify that TGFβ signalling was measured in this reporter assay, sera were treated with anti-TGFβ1/2/3 for 1 hour at RT before use. Results: Control sera significantly induced reporter activity by 4.5-fold. However, SSc sera only induced a 2.5-fold increase in luciferase activity, indicating significantly lower bioactivity of TGFβ (p<0.0001). This difference was not due to a difference in total TGFβ levels; after activation of all TGFβ both HC and SSc sera induced a similar 6-fold increase in signal strength. These data show that in HC sera approximately 75% of all TGFβ is bioactive compared to only 42% in SSc. Addition of anti-TGFβ1/2/3 inhibited all CAGA12 -luc reporter activity (p<0.0001) of both HC and SSc serum, and of both acidified and not acidified sera (p<0.0001), showing that our bioassay is indeed TGFβ-dependent. To investigate if reduced bioactivity is a more general phenomenon we measured BMP activity. BMP proteins are structurally closely related to TGFβ and also circulate in inactive form. Both HC and SSc sera induced a similar 8-fold increase in BRE-luc activity, and this activity was increased to a 16-fold induction after acidification for both groups. BMPs in SSc sera are thus not less bioactive. This illustrates the uniqueness of our observation on TGFβ bioactivity. Conclusions: TGFβ in SSc serum is less bioactive than in control serum whereas BMPs are not less bioactive. Disclosure of interest: None declared